Grundtvig oversat til tysk salmetradition. Med resumé på tysk: Grundtvig auf Deutch - Albertsen, L. L. (Grundtvig-studier, 1970)
Grundtvig translated to German hymn-tradition. With summary in German: Grundtvig auf Deutch By L. L. Albertsen